KONTRIBUSI SUPERVISI PENGAWAS PAI DAN KEPALA SEKOLAH UNTUK MENINGKATKAN PROFESIONALITAS GURU PADA SMK SE-KABUPATEN GUNUNGKIDUL - Suroto Suroto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2017)
The supervision of PAI (Islamic Education subject) supervisor and headmaster is an important factor in improving low teacher professionalism. This study aimed to identify how much PAI supervisor’s supervision (X1) and headmaster’s supervision (X2) contributed towards teacher professionalism (Y). This research was an associative study with a quantitative approach. The data collection technique used questionnaires and documentations for the respondent population as much as 72 PAI teachers of all vocational high schools in Gunungkidul Regency. The results showed that: (1) There was a significant positive correlation between X1 and Y (rX1Y = 0.468), the contribution of X1 to Y, as much as 21.90%, was considered small, while the remaining 78.10% was the contribution of other variables excluded from the study, (2) There was a significant positive correlation between X2 and Y (rX2Y = 0.55), the contribution of X2 to Y, as much as 30.25%, was considered small, while the remaining 69.75% was the contribution of other variables excluded from the study, (3) There was a significant positive correlation between X1 and X2 (all together) and Y (rX1X2Y = 0.613), the contribution of X1 together with X2 to Y, as much as 37.58%, was considered small, while the remaining 62.42% was the contribution of other variables excluded from the study. Based on these results, the researcher would recommend the PAI supervisor and headmaster of all vocational high schools in Gunungkidul Regency (1) to improve the aspect of supervision follow-up considering that this aspect was the lowest among the aspects of supervision planning and supervision implementation, (2) to improve supervision synergy/cooperation between the PAI supervisor and headmaster, and the PAI teachers of all vocational high schools in Gunungkidul Regency should improve the teaching-learning implementation considering that this aspect was the lowest compared to the aspects of lesson planning and evaluation.